Postnatal Care Services Utilization in Bharatpur Sub Metropolitan City, Chitwan, Nepal - Shrestha, Niki; Tiwari, Binita; Piryani, Suneel; Khanal, Gayatri (Journal of Chitwan Medical College, 2019)
Background: Postnatal period is a critical phase in the lives of mothers and newborn infants. 2.9 million neonatal deaths occur in the first week of life on an annual basis globally. In Nepal, the level of postnatal care coverage remains low despite the efforts and research on factors influencing the Post-natal care (PNC) services utilization is limited. Hence this study was conducted to explore the predictors of PNC utilization among mothers who had under one-year child. Methods: A community-based cross-sectional study was conducted in Bharatpur Sub Metropolitan city, Chitwan among mothers having a child of less than one year age. Data was collected through face-to-face interview using interview-schedule. Descriptive (frequency and percentage), Bivariate (Chi-squre) and Multivariate (logistic regression) analyses were performed. Results: This study showed that the proportion of recommended PNC services utilization is low in comparison with those utilizing ANC services in Nepal. The percentage of women attending all the three recommended PNC visits was only 17.5%. The utilization of PNC services was associated with mother’s educational status, parity, place of PNC services received and awareness about PNC services. The mode of delivery, danger signs seen in postnatal mothers, and danger signs seen in newborn were statistically significantly associated with PNC services utilization. Conclusions: The findings of this study suggest context specific evidence which might be taken into consideration while planning to develop new policies to increase PNC utilization.